Myofascial pain syndrome - Nicola Maratea (Publiediting, 2020)
Among the musculoskeletal pain syndromes, myofascial is certainly one of the most frequent. Overuse musculoskeletal pain affects 33% of adults and is responsible for 29% of work days lost due to illness. Myofascial pain syndrome (MPS) is a condition characterized by local pain is reportedly, described as dull and deep, determined by the presence of myofascial trigger points. Trigger points (TP) are areas of hypersensitivity localized in one or more muscles that evoke pain referred to at a distance in the so-called target areas. The acupressure of TP remotely evokes pain referred to in the so-called target area (or reference area) and a localized muscle contraction (twitch). The genesis of trigger points is multifactorial and includes morphological, neurotransmitter, neuro sensitive and electrophysiological changes. Therapy can make use of various choices: anesthetic block of trigger points, stretch and spray, localized pressure at the level of TP, non-steroidal analgesics and adjuvants such as octreotide by endocular route and active physical therapy.